Hematopoietic neoplasms in Prkar2a-deficient mice. Issue 1 (December 2015) - Saloustros, Emmanouil; Salpea, Paraskevi; Qi, Chen-Feng; Gugliotti, Lina; Tsang, Kitman; Liu, Sisi; Starost, Matthew; Morse, Herbert; Stratakis, Constantine
Abstract Background Protein kinase A (PKA) is a holoenzyme that consists of a dimer of regulatory subunits and two inactive catalytic subunits that bind to the regulatory subunit dimer. Four regulatory subunits (RIα, RIβ, RIIα, RIIβ) and four catalytic subunits (Cα, Cβ, Cγ, Prkx) have been described in the human and mouse genomes. Previous studies showed that complete inactivation of thePrkar1a subunit (coding for RIα) in the germline leads to embryonic lethality, whilePrkar1a –deficient mice are viable and develop schwannomas, thyroid, and bone neoplasms, and rarely lymphomas and sarcomas. Mice with inactivation of thePrkar2a andPrkar2b genes (coding for RIIα and RIIβ, respectively) are also viable but have not been studied for their susceptibility to any tumors. Methods Cohorts ofPrkar1a +/−, Prkar2a +/−, Prkar2a −/−, Prkar2b +/− and wild type (WT) mice have been observed between 5 and 25 months of age for the development of hematologic malignancies. Tissues were studied by immunohistochemistry; tumor-specific markers were also used as indicated. Cell sorting and protein studies were also performed. Results BothPrkar2a −/− andPrkar2a +/− mice frequently developed hematopoietic neoplasms dominated by histiocytic sarcomas (HS) with rare diffuse large B cell lymphomas (DLBCL). Southern blot analysis confirmed that the tumors diagnosed histologically as DLBCL were clonal B cell neoplasms. Mice with other genotypes did not develop a significant number of similar neoplasms. Conclusions Prkar2a deficiency predisposes to hematopoietic malignancies in vivo. RIIα's likely association with HS and DLBCL was hitherto unrecognized and may lead to better understanding of these rare neoplasms.